Implementación de un Manual de Control Interno de Inventario en el Taller de “Importadora Tomebamba S.A.” de la ciudad de Machala, año 2023 - Guerrero Lucio, Oscar Eduardo (2024)
The present curricular integration work titled "Implementation of an Internal Inventory Control Manual at the Auto Repair Shop of Importadora Tomebamba S.A. in the city of Machala, 2023" was developed to propose an instrument that provides the company with guidelines and mechanisms for improved decision-making. The general objective was achieved by establishing a manual of policies and procedures aimed at effective and efficient inventory management. This allowed to achieve the stated objectives; thus, research techniques were applied, including observation, interviews, and internal control questionnaires aimed at the manager, accounting assistant, and other employees, revealing different deficiencies in internal control and the lack of a manual for policies and control procedures, causing risks that affect the optimization of the company's resources. The manual implementation will allow for the optimization of inventory management, the reduction of associated risks, and the improvement of the company's requirements, aiming to reinforce the control of spare parts, supplies, and accessories in the auto repair shop. This will enable staff to understand the significant guidelines and tasks that should be carried out for the processes of acquisition, reception, storage, and dispatch of inventory, in which good practices and activities are mentioned for better internal organizational control. Additionally, it establishes responsibilities and roles for employees involved in inventory management. Finally, this research concludes that the auto repair shop's operations can significantly benefit from a more structured inventory management system. Having a manual of policies and procedures will enhance inventory management according to the auto repair shop's needs, providing workers with a useful and easy-to-understand tool for their daily activities. Furthermore, to ensure the effectiveness of these guidelines, it is recommended that management conduct ongoing monitoring to guarantee the manual effectively supports decision-making. In this regard, a manual of specific policies and procedures is proposed for the control of the auto repair shop warehouse at “Importadora Tomebamba S.A.”.